Characterization of Penaeus vannamei mitogenome focusing on genetic diversity. - Paulo Eduardo T Soares; Márcia Danielle A Dantas; Rita de Cássia B Silva-Portela; Lucymara F Agnez-Lima; Daniel Carlos F Lanza (PLoS ONE, 2021)
The diversity of the Penaeus vannamei mitochondrial genome has still been poorly characterized, there are no validated mitochondrial markers available for populational studies, and the heteroplasmy has not yet been investigated in this species. In this study, metagenomic reads extracted from the muscle of a single individual were used to assemble the mitochondrial genome (mtDNA). These data associated with mitochondrial genomes previously described allowed to evaluate the inter-individual variability and heteroplasmy. Comparison among 45 mtDNA control regions led to the detection of conserved and variable segments and the characterization of two hypervariable regions. The analysis of diversity revealed mostly low frequency polymorphisms, and heteroplasmy was found in practically all mitochondrial genes, with a high occurrence of indels. These results indicate that the design of mitochondrial markers for P. vannamei must be done with caution. The mapping of conserved and variable regions and the characterization of heteroplasmy presented here will contribute to increasing the efficiency of mitochondrial markers for population or individual studies.